Primary cardiac composite hemangioendothelioma with calcification mimicking a right atrial myxoma: A rare entity. Issue 11 (8th September 2022) - Zhou, Xiang; Liu, Hongyan; He, Jiahui; Cheng, Youping; Lu, Jiajia
Abstract: Composite hemangioendothelioma (CHE) is a rare vascular tumor which shows varying combination of benign, low‐grade, and malignant vascular components on pathology. CHE is usually located on the surface of the dermis and subcutaneous tissue of the extremities. We report an unusual case of CHE in the heart.